Impact of GBA1 variants on long-term clinical progression and mortality in incident Parkinson's disease. Issue 7 (17th April 2020) - Stoker, Thomas B; Camacho, Marta; Winder-Rhodes, Sophie; Liu, Ganqiang; Scherzer, Clemens R; Foltynie, Thomas; Evans, Jonathan; Breen, David P; Barker, Roger A; Williams-Gray, Caroline H
Abstract : Introduction: Variants in the GBA1 gene have been identified as a common risk factor for Parkinson's disease (PD). In addition to pathogenic mutations (those associated with Gaucher disease), a number of 'non-pathogenic' variants also occur at increased frequency in PD. Previous studies have reported that pathogenic variants adversely affect the clinical course of PD. The role of 'non-pathogenic' GBA1 variants on PD course is less clear. In this study, we report the effect of GBA1 variants in incident PD patients with long-term follow-up. Methods: The study population consisted of patients in the Cambridgeshire Incidence of Parkinson's disease from General Practice to Neurologist and Parkinsonism: Incidence, Cognition and Non-motor heterogeneity in Cambridgeshire cohorts. Patients were grouped into non-carriers, carriers of 'non-pathogenic' GBA1 variants and carriers of pathogenic GBA1 mutations. Survival analyses for time to development of dementia, postural instability and death were carried out. Cox regression analysis controlling for potential confounders were used to determine the impact of GBA1 variants on these outcome measures. Results: GBA1 variants were identified in 14.4% of patients. Pathogenic and 'non-pathogenic' GBA1 variants were associated with the accelerated development of dementia and a more aggressive motor course. Pathogenic GBA1 variants were associated with earlier mortality in comparison with non-carriers, independent of the development of dementia. Discussion: GBA1 variants, including those not associated with Gaucher disease, are common in PD and result in a more aggressive disease course.